2008
DOI: 10.4315/0362-028x-71.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Listeria monocytogenes in Cull Sows and Pork

Abstract: The goal of this study was to determine the prevalence of Listeria monocytogenes in sows slaughtered at a single Midwestern plant on two occasions (trial 1, n = 179 sows; trial 2, n = 160 sows). Fecal samples collected antemortem (trial 1) as well as animal tissues, and carcass swabs collected at the abattoir (trials 1 and 2) were analyzed. Eight isolates of L. monocytogenes were recovered from five samples that represented 0.18% of the total samples (n = 2,775). In trial 1, L. monocytogenes was detected in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…In our study, the strains of serogroup IVb presented a 3-amino-acid deletion in the inlA sequence that has been linked with highly invasive strains (33). The presence of strains of this serogroup in the feces of live pigs has already been described, supporting the evidence that live pigs may introduce these strains into meat processing plants (7,53). Despite the low contamination level found in lairage pens, a variety of pulsotypes was found.…”
Section: Strain (Pulsotype)supporting
confidence: 79%
See 3 more Smart Citations
“…In our study, the strains of serogroup IVb presented a 3-amino-acid deletion in the inlA sequence that has been linked with highly invasive strains (33). The presence of strains of this serogroup in the feces of live pigs has already been described, supporting the evidence that live pigs may introduce these strains into meat processing plants (7,53). Despite the low contamination level found in lairage pens, a variety of pulsotypes was found.…”
Section: Strain (Pulsotype)supporting
confidence: 79%
“…The strain associated with this outbreak was of serovar l/2a (serogroup Ila). This serovar was also linked to a cheese-associated outbreak that occurred in the same year animals (5,30,53). L. monocytogenes has been found in the feces, intestines, and tonsils of healthy pigs on farms at levels ranging from 0 to 61% (16,30,47,53).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, the organism is able to adhere and persist for long periods on the surface of equipment forming biofilms (Kornacki and Gurtler, 2007). L. monocytogenes can be found at all stages of pork meat industry with increasing prevalence from the slaughterhouse to the cutting room (Thénevot et al, 2006a;López et al, 2008;Wesley et al, 2008). Our results could confirm our previous study carried out on raw minced pork which showed that 35.0% and 8.0% of the samples examined proved positive for Listeria spp.…”
Section: Resultssupporting
confidence: 89%